D-H Parameter Method-based Wearable Motion Tracking. Issue 1 (1st March 2022) - Qian, Huizu; Chen, Benbin; Xia, Xuke; Deng, Shengzhong; Wang, Yuxiang
Abstract: Motion capture is a key technology for robots to accurately understand pedestrian intentions in the scene of human-machine integration. Due to the limited spatial distance and easy obstruction by obstacles, traditional optical motion capture systems often lose detection targets. This paper proposes a wearable motion tracking method based on D-H parameter method. By binding multiple wireless inertial sensor units composed of accelerometers, magnetic flux sensors and gyroscopes to various moving parts of the user's body, accurate and robust tracking of moving targets is achieved. This method uses the known pose information of the root node to find the pose state of each level in the reference coordinate system, and establishes the human body joint rotation model and the bone position state model. The results show that the motion tracking method proposed in this paper reduces 9 degrees of freedom compared with the traditional forward kinematics method, and the algorithm efficiency is increased by about 20%, which can accurately obtain the posture characteristics of the human body. It can be seen that the D-H parameter method is reasonable for the wearable human body motion tracking.